Percutaneous Nephrolithotomy (PCNL) for Management of Renal Stone in Pediatric Patient- Single Center Experience - Bhuiyan, NI; Tawhid, KMH; Islam, MF; Bhuiyan, Zahid H; Ahmed, NIU; Salahuddin, K; Arafat, MA (Journal of Surgical Sciences, 2019)
Introduction: Percutaneous nephrolithotomy (PCNL) is already an established method of management of renal stone in Bangladesh. Initially the procedure was restricted to adult age group only. Percutaneous Nephrolithotomy is the choice of procedure for management of renal stone in paediatric age group. Objectives: To see the out come of stone clearance by Percutaneous Nephrolithotomy(PCNL)in paediatric age group. Methods: This was a study in single centre since January' 09 to December 201 1 . Total 1 1 cases of renal stone in paediatric age group were managed by PCNL. The age ranges from 4 years to 15years, average 8.47 years. We use pneumatic lithotripters. Nephrostomy tubes and D-J stent were used in 7 cases. In 4 cases only DJ stent were used. Postoperative haematocrit and creatinine was measured routinely. Results: Total stone clearance was achieved in all cases. The major post-operative complication was urosepsis(n-1), managed conservatively. Total hospital stay was 3 to 5 days; average 3.5 days. Stents were removed after 2 weeks. Conclusions: PCNL is a suitable procedure for the management of renal stone in pediatric age group this needs expertise, longer learning curve under supervised training. Journal of Surgical Sciences (2012) Vol. 16 (2) : 76-79